ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA TENAGA PENJUALAN STUDI PADA PT. NASMOCO JAWA TENGAH DAN DIY - Amri, Syaeful (Master of Management Diponegoro University, 2014)
The purpose of this research was to test the influences of of learning orientation, quality oftraining, sales force competence, smart working orientation toward sales force performanceto achieve sales targets. The usage of these variables was able to solve the arising problemwithin PT. Nasmoco Central Java and DIY.The Research aims to analyze the influences of factors toward performance of sales force,based on the case, a theoretical model and 4 hypotheses are accomplished to be testedusing Structural Equation Model (SEM). The sample of this research is 100 sales person inPT. Nasmoco Jawa Tengah and DIY.From the result of this analysis, Structural Equation Model has fulfilled criteria of GoodnessFit Index; X2 (chi square) 100,219, probability 0.109 (eâ€0.05), RMSEA 0.044 (dâ€0.08), GFI0.887 (eâ€0.90), AGFI 0.838 (eâ€0.90), TLI 0.985 (eâ€0.95), CFI 0.988 (eâ€0.95).The result of the analysis showed that learning orientation, quality of training, and sales forcecompetence strongness an positive influence, which is significant to sales force performanceand sales targets. The empirical result indicated that to increase sales targets of PT. NasmocoCentral Java and DIY, management need to pay attention on factors learning orientation,quality of training, sales force competence, and sales force performance, because that is thefactors that effect high or low level of achieving sales targets.